Cost-benefit analysis of vaccination against goat pox - BARDHAN, D; KUMAR, SANJAY; KUMAR, SHIV; SINGH, R P; HOSAMANI, M (The Indian Journal of Animal Sciences, 2020)
The present study has quantified the economic impact of control of goat pox disease in India using a vaccine developed against the disease at ICAR-IVRI, applying an economic surplus model. The findings of the study have revealed significant benefits of Goat pox control programme using the vaccine. The potential change in total surplus, as a result of Goat pox control programme was ₹ 2.42 crore/annum. The change in total economic surplus and research and delivery cost were projected from 1999 (year of the start of the project) to 2030 after adjusting for the above adoption pattern. Using a long run discount rate of 7.50%, the benefits were compared to research and delivery cost and the NPV, IRR and BCR were calculated. The NPV, IRR and BCR of Goat pox control programme were ₹ 9.25 billion, 38% and 19: 1, respectively. Sensitivity analysis revealed that the benefits are most sensitive to assumptions regarding lower degree of immunity offered by the vaccine and higher discount rate.